The Preventive Maintenance Practices and Performance among Manufacturing Organizations in Malaysia; the Moderating Role of Technological Capabilities - Sasitharan, Dayanan (2020)
The importance of maintenance has become the main focus in the manufacturing environment. New technologies and advancements in the manufacturing industry have driven many companies to implement reliable maintenance program in order to avoid stoppages and disruptions of equipment from occurring in their daily operations. The purpose of this study was to examine the preventive maintenance (PM) practices and performance among manufacturing organizations in Malaysia, and the technological capabilities (TC) used as a moderator in the relationship between preventive maintenance practices and performance among Malaysian manufacturing organizations. The correlations between three components of PM, namely time-based maintenance (TBM), condition-based maintenance (CBM) and predictive maintenance (PdM),:and manufacturing performance dimensions (cost; quality; flexibility and delivery) were evaluated and validated by employing Smart-PLS statistical tools. 600 questionnaires were circulated to various manufacturing organizations in all regions of Malaysia. However, only 155 questionnaires were returned and were usable for analysis. Correlation analysis was carried out and the results show that there is a positive relationship among PM practices. In general, PM practices, for instance predictive maintenance show positive and significant correlations among this sample of Malaysian manufacturing organizations. Meanwhile, the hypothesis result indicates that the performance of the manufacturing organizations is only influenced by PdM and the TBM and CBM practices, fail to positively influence manufacturing performance. In addition, the moderation analysis indicates that the TC not positively moderate TBM, CBM and PdM toward manufacturing performance. The overall results suggest that PdM practices can be identified as one of the best strategies to face stiff competitive environments in enhancing the effectiveness of quality improvement among Malaysian manufacturing organizations.